2015
DOI: 10.1186/s12889-015-2551-2
|View full text |Cite
|
Sign up to set email alerts
|

Do discrimination, residential school attendance and cultural disruption add to individual-level diabetes risk among Aboriginal people in Canada?

Abstract: BackgroundAboriginal peoples in Canada (First Nations, Metis and Inuit) are experiencing an epidemic of diabetes and its complications but little is known about the influence of factors attributed to colonization. The purpose of this study was to investigate the possible role of discrimination, residential school attendance and cultural disruption on diabetes occurrence among First Nations adults.MethodsThis 2012/13 cross sectional survey was conducted in two Saskatchewan First Nations communities comprising 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…In a previous study of 13 First Nations com munities in Alberta, communities with higher knowledge of Indigen ous language had significantly lower diabetes preva lence. 29 In contrast, Dyck and colleagues 30 found that individual level cultural disruption was not predictive of diabetes risk and that Cree language use was not a protective factor. These complex interactions among land, culture, environment, community, col onial disruption and risk of diabetes are best understood using a framework based on Indigenous determinants of health.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study of 13 First Nations com munities in Alberta, communities with higher knowledge of Indigen ous language had significantly lower diabetes preva lence. 29 In contrast, Dyck and colleagues 30 found that individual level cultural disruption was not predictive of diabetes risk and that Cree language use was not a protective factor. These complex interactions among land, culture, environment, community, col onial disruption and risk of diabetes are best understood using a framework based on Indigenous determinants of health.…”
Section: Discussionmentioning
confidence: 93%
“…Howard [ 31 ] found similar results and suggested that residential schooling contributed to the urbanization of Indigenous peoples in Canada, which has led to diabetes and other problems. Dyck and colleagues also reported that those who attended residential school had a slightly higher prevalence of diabetes than those who did not, although the finding was not statistically significant [ 32 ]. Residential school attendance has also been found to be a positive predictor of obesity among younger Métis boys and girls, but a negative predictor among older girls [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants were recruited through similar methods from the same communities, with similar health status and characteristics. As social determinants of health, including education, income, and employment are known to influence health outcomes, and disproportionately affect Indigenous Canadians, similarities of these determinants between groups facilitate comparisons while minimizing confounding variables (Rotenberg 2016;Dyck et al 2015). In this investigation, hypertension was only associated with obesity measures and statuses among Europeans.…”
Section: Discussionmentioning
confidence: 76%
“…Conversely, we identified Indigenous populations experiencing lower hypertension rates than non-Indigenous populations (Foulds and Warburton 2014). Indigenous Canadians also experience greater burdens of social determinants of health and racism (Rotenberg 2016;Dyck et al 2015). Few comparisons of vascular measures among ethnic groups including Indigenous populations have been conducted to date, none evaluating PWV, BRS, or arterial compliance among Indigenous adults (Anand et al 2001;Zhang et al 2013).…”
Section: Introductionmentioning
confidence: 99%